Gender Based Violence in Botswana: A Moral Perspective - Stephen Pabalelo Nawa (Universitas Negeri Makassar, 2022)
This paper discusses two moral theories with the aim of arguing against gender-based violence (GBV) in Botswana, particularly violence against women (VAW). The first moral theory is the African ethic of Ubuntu/botho according to which actions are right insofar as they promote harmonious relationships where people can live in solidarity with one another. The second is Immanuel Kant’s moral theory according to which actions are right provided they are done purely from duty, otherwise they are wrong. After spelling out the tenets of each theory, the paper applies it to instances of GBV to show that it is essentially morally wrong. More specifically, the paper employs these moral theories to demonstrate that GBV violates human dignity of its victims; that it undermines their health, security and autonomy. This paper uses the method of critical and conceptual analysis which consists in analyzing concepts or ideas to understand their meanings.